Determining Factor of Village Financial Managers Moderated by Coworker Support - Widianto, Andri; Sari, Yeni Priatna; Faidah, Yusri Anis; Artanti, Destiana (Institut Bisnis dan Informatika Kesatuan, 2026)
The success of a village is determined by its vision and mission, but it also depends on the quality and capabilities of the village officials. The performance of village financial managers is influenced by individual capabilities and responsibilities; however, other factors also play a role. This study seeks to ascertain the effect of work-life balance and job stress on the performance of village financial managers, with peer support serving as a moderating variable. This quantitative analysis utilized primary data collected via an online questionnaire. The respondents in this study were 51 village finance managers in the Banjarharjo Subdistrict of Brebes Regency. Incidental sampling was used in this study. In addition, the data was analyzed utilizing the Partial Least Squares technique. The findings of the examination support all hypotheses that work-life balance and job stress significantly affect performance. Village financial managers who can maintain a balance between work and personal life show more optimal performance, while job stress that is not managed properly has been proven to reduce work effectiveness. In addition, the results of this study validate that coworker support plays a significant role in moderating these two relationships.